2016
DOI: 10.1007/s11255-016-1323-y
|View full text |Cite
|
Sign up to set email alerts
|

A propensity score-matched comparison of surgical precision obtained by using volumetric analysis between robot-assisted laparoscopic and open partial nephrectomy for T1 renal cell carcinoma: a retrospective non-randomized observational study of initial outcomes

Abstract: RAPN can offer acceptable surgical outcomes and precision, compared to OPN, with decreased estimated blood loss and hospital stay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 24 publications
2
26
0
Order By: Relevance
“…suggests reduced operative complications, EBL and length of hospital stay in RAPN . Recent studies reinforce these findings . Similarly, our study demonstrated with statistical significance a benefit of RAPN over OPN in these perioperative parameters.…”
Section: Discussionsupporting
confidence: 89%
“…suggests reduced operative complications, EBL and length of hospital stay in RAPN . Recent studies reinforce these findings . Similarly, our study demonstrated with statistical significance a benefit of RAPN over OPN in these perioperative parameters.…”
Section: Discussionsupporting
confidence: 89%
“…We previously compared surgical outcomes between RAPN and OPN using a propensity‐matched study design, and we showed feasible deterioration of the eGFR with a mean WIT of 18 min in the RAPN group and mean cold ischemia time of 38 min in the OPN group. In addition, RAPN tended to preserve more renal parenchymal volume than OPN, although this was not statistically significant ( P = 0.05) . However, that previous study included all patients who underwent RAPN and OPN during the study period.…”
Section: Discussionmentioning
confidence: 83%
“…However, several different surgeons carried out OPN, although they were supervised by the aforementioned three specific surgeons. The methods of OPN and RAPN were described in our previous report . In OPN, all surgeries were carried out under cold ischemia.…”
Section: Methodsmentioning
confidence: 99%
“…Thirty‐four eligible studies included 60 808 patients who underwent PN, of whom 19 638 underwent RaPN with mean age 58.9 years and 41 170 underwent OPN with mean age 58.5 years. Table presents the baseline patient demographics of all enrolled studies.…”
Section: Resultsmentioning
confidence: 99%
“…It could be deduced that RaPN is favorable in renal function preservation due to factors other than renal pedicle control. Takagi et al revealed that RaPN tended to preserve more normal parenchyma than OPN (84% versus 79%, P = 0.0504). RaPN also provided narrower peritumoral surgical margin than OPN due to improved vision with 3D capabilities .…”
Section: Discussionmentioning
confidence: 98%